2013
DOI: 10.1293/tox.2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Characterization of a Renal Nephroblastoma in a <i>Trp</i>53-mutant and Prolyl Isomerase 1-deficient Mouse

Abstract: A nephroblastoma is a tumor arising from metanephric blastema occurring in childhood. Among laboratory rodents, nephroblastoma has been frequently reported in rats, but it remains exceedingly rare in mice. The present work describes a nephroblastoma in a young mouse homozygous for the specific Trp53 R172H point mutation coupled with targeted deletion of the Pin1 gene. The affected kidney was effaced by a biphasic tumor with an epithelial component arranged in tubules surrounded by nests of blastemal cells. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Instead, in this report we found in this case that the blastema cells were negative for cytokeratin and vimentin, which is in agreement with Castiglioni et al (2013), and marked positive for S100. The mesenchymal cells are marked positive for vimentin and smooth muscle actin, which is in agreement with Yamamoto et al (2006), which may demonstrate that these cells are differentiating into smooth muscle tissue (CASTIGLIONI et al, 2013).…”
Section: Introductionsupporting
confidence: 77%
“…Instead, in this report we found in this case that the blastema cells were negative for cytokeratin and vimentin, which is in agreement with Castiglioni et al (2013), and marked positive for S100. The mesenchymal cells are marked positive for vimentin and smooth muscle actin, which is in agreement with Yamamoto et al (2006), which may demonstrate that these cells are differentiating into smooth muscle tissue (CASTIGLIONI et al, 2013).…”
Section: Introductionsupporting
confidence: 77%
“…Generally, genetic variation or abnormal embryonic development of the genitourinary tract may play a part in its pathogenesis. WT is also considered a prototype of differentiation failure (Emerson et al, 2004;Grieco et al, 2006;Castiglioni et al, 2013). Nevertheless, the cell origin of WT is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Vittoria et al reported the development of nephroblastoma in a young C57BL/6 mouse with a Pin1 deletion coupled with a Trp53 abnormality. This discovery provides novel insights into the relationship between Pin1 and nephroblastoma tumor pathogenesis ( Castiglioni et al, 2013 ).…”
Section: Effects Of Pin1 On Kidney Diseasementioning
confidence: 99%